Health Education Using Leaflets Increases Diet Compliance in Hypertension Patients - Yunarti, Wiyan Sri; Mawaddah, Nurul; Mujiadi, Mujiadi (PT Saintek Medika Nusantara, 2023)
During the Covid-19 pandemic, the death rate has increased in patients with hypertension. This study aims to determine the effectiveness of health education using leaflets on dietary compliance of hypertension patients. This study used a pre-experimental research design with a pretest posttest one group design approach. The population in this study were 160 hypertension patients at the Heart Polyclinic of Gatoel Hospital, Mojokerto. The sampling technique used consecutive sampling. The sample size was 20 people. The research instrument used a questionnaire. Data analysis used the Wilcoxon Signed Ranks Test. The results showed that there was an increase in the number of respondents who were compliant with the hypertension diet, which previously had no compliant respondents, increasing to 16 compliant respondents from 20 samples. The results of the data analysis showed the effectiveness of health education using leaflets on dietary compliance of hypertension patients at the heart disease polyclinic of Gatoel Hospital, Mojokerto, as evidenced by the results of the Wilcoxon Signed Ranks test which showed that p value = 0.005 or <α (0.05) so that H1 was accepted. The conclusion of the results of this study is that health education using leaflets is effective. Hypertensive patients are expected to implement a hypertension diet so that blood pressure can be controlled.